2008
DOI: 10.1002/humu.20780
|View full text |Cite
|
Sign up to set email alerts
|

UMD-USHbases: a comprehensive set of databases to record and analyse pathogenic mutations and unclassified variants in seven Usher syndrome causing genes

Abstract: Using the Universal Mutation Database (UMD) software, we have constructed "UMD-USHbases", a set of relational databases of nucleotide variations for seven genes involved in Usher syndrome (MYO7A, CDH23, PCDH15, USH1C, USH1G, USH3A and USH2A). Mutations in the Usher syndrome type I causing genes are also recorded in non-syndromic hearing loss cases and mutations in USH2A in non-syndromic retinitis pigmentosa. Usher syndrome provides a particular challenge for molecular diagnostics because of the clinical and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…12,21,26 All of these mutations occurred by transition (C/G-T/A) at CpG sites and were considered to be recurrent, which meets the fact that they are not specific to a particular ethnic group. This finding is consistent with a result of an analysis by Baux et al, 27 who reported that a high proportion of MYO7A and CDH23 mutations are represented by single base-pair substitutions and that 51.5 and 48.5% of them in MYO7A and CDH23, respectively, involve a CpG dinucleotide. Interestingly, neither of the two novel mutations found in the present study is of the transition type.…”
Section: Discussionsupporting
confidence: 92%
“…12,21,26 All of these mutations occurred by transition (C/G-T/A) at CpG sites and were considered to be recurrent, which meets the fact that they are not specific to a particular ethnic group. This finding is consistent with a result of an analysis by Baux et al, 27 who reported that a high proportion of MYO7A and CDH23 mutations are represented by single base-pair substitutions and that 51.5 and 48.5% of them in MYO7A and CDH23, respectively, involve a CpG dinucleotide. Interestingly, neither of the two novel mutations found in the present study is of the transition type.…”
Section: Discussionsupporting
confidence: 92%
“…Mutations that lead to predicted CDH23 null alleles cause USH1D (Fig. 2D) (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12), which is modeled by mutations in waltzer mice (Fig. 2D) (27,33,34).…”
Section: Resultsmentioning
confidence: 99%
“…The cadherin 23 gene (CDH23) provides a striking example. Predicted CDH23 null mutations lead to deaf-blindness (USH1D), whereas missense mutations cause nonsyndromic deafness (DFNB12) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). A polymorphism in Cdh23 is linked to age-related hearing loss (14).…”
mentioning
confidence: 99%
“…A great majority of these mutations are private or present in a few families. 14 However, a prevalent mutation located in exon 13, designated as c.2299delG, is frequently found in the European and US patients, and also in isolated cases from South America, South Africa and Asia. The allele frequency distribution of c.2299delG varies geographically in Europe.…”
Section: Introductionmentioning
confidence: 99%